Impact of MIF Gene Promoter Variations on Risk of Rheumatic Heart Disease and Its Age of Onset in Saudi Arabian Patients - Abdallah, Atiyeh M.; Al-Mazroea, Abdulhadi H.; Al-Harbi, Waleed N.; Al-Harbi, Nabeeh A.; Eldardear, Amr E.; Almohammadi, Yousef; Al-Harbi, Khalid M. (Frontiers in Immunology, 2016)
Although macrophage migration inhibitory factor (MIF) has consistently been shown to be an important immune modulator, data on the association between MIF promoter variations and the risk of developing rheumatic heart disease (RHD) remain inconclusive. RHD remains an important complication of streptococcal infections in the Middle East, not least in Saudi Arabia, and identifying risk markers remains an important priority. Therefore, we investigated the association between two functional MIF promoter variations and RHD susceptibility and severity in Saudi patients: the MIF-173G>C substitution (rs755622) and the MIF-794 CATT5-8 tetra-nucleotide repeat (rs5844572). 326 individuals (124 RHD patients and 202 age-, sex-, and ethnically-matched healthy controls) were genotyped using allelic discrimination and fragment analysis. Data were analyzed with respect to disease susceptibility, severity, sex, and age of onset. There was a significantly lower frequency of 173C allele carriage in RHD patients compared to controls (OR = 0.47; 95% CIs = 0.28-0.77; p = 0.003). Interestingly, the 173C allele was associated with late disease onset (p = 0.001). The 794 5-repeat allele was associated with decreased RHD risk (OR = 0.56; 95% CIs = 0.38-0.82; p = 0.003). In contrast, the 794 6-repeat allele was associated with increased risk of RHD (OR = 1.7; 95% CIs = 1.2-2.5; p = 0.002). MIF promoter variations appear to have a dual role in RHD, with 173C allele non-carriers at higher risk of developing RHD at a younger age. These results require further validation in larger multi-ethnic cohorts, and functional studies are necessary to understand the underlying molecular mechanisms driving the at-risk phenotype.